2014
DOI: 10.1002/macp.201400110
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fluorescence Quenching of 2‐Thiohydantoin‐Containing Conjugated Polymers: Applications for Ion Sensing

Abstract: A novel poly(phenylene ethynylene) containing 2‐thiohydantoin [poly(1)] is synthesized. The addition of F− quenches the fluorescence, while the fluorescence of the solution only changes slightly upon addition of other anions, indicating the sensing ability of poly(1) toward F−. The addition of Ag+ quenches the fluorescence of the polymer, whereas the addition of other metal ions results in only slight changes to the fluorescence. Compared with its small‐molecule counterpart, the Stern–Volmer quenching constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 97 publications
0
1
0
1
Order By: Relevance
“…在溶液中, 阴阳离子往往是同时出现, 阴阳离子平 衡对生物体具有极其重要的影响, 而对于阴阳离子的同 时检测是一个较大的挑战 [27] . 黄飞鹤课题组 [28] [29] 利用 Sonogashira 反 应, 合成了"turn-on"型有机聚合物荧光传感器(Eq.…”
Section: 基于直接聚合法的有机聚合物荧光传感器unclassified
“…在溶液中, 阴阳离子往往是同时出现, 阴阳离子平 衡对生物体具有极其重要的影响, 而对于阴阳离子的同 时检测是一个较大的挑战 [27] . 黄飞鹤课题组 [28] [29] 利用 Sonogashira 反 应, 合成了"turn-on"型有机聚合物荧光传感器(Eq.…”
Section: 基于直接聚合法的有机聚合物荧光传感器unclassified
“…Fluorescent chemosensors (FCs) are advantageous over other types of sensors, since FCs have higher sensitivity and selectivity, and enable scientist to perform real‐time monitoring with fast response time . A substantial amount of scientific efforts have been focused on the design and development of polymeric sensors having molecular recognition and signaling sites . Zeng et al reported polyfluoreneethynylene FC with carboxylic acid side groups for the sensing of Cu(II) ion .…”
Section: Introductionmentioning
confidence: 99%